Effects of strength training with elastic band programme on fitness components in young female handball players: a randomized controlled trial - Hammami, Mehrez; Gaamouri, Nawel; Wagner, Herbert; C Pagaduan, Jeffrey; Hill, Lee; T Nikolaidis, Pantelis; Knechtle, Beat; Souhaiel Chelly, Mohamed (Biology of Sport, 2022)
This study examined the effect of a 10-week programme of strength training with elastic band (STEB) on fitness components in young female handball players. Twenty-six young female handball players (aged 15.8 ± 0.2 years) from the same club participated in this study. They were randomly assigned between experimental (EG; n = 13) and control (CG; n = 13) groups. The EG performed the STEB, replacing some handball-specific drills in the regular handball training. The CG followed the regular handball training (i.e., mainly technical-tactical drills, small sided and simulated games, and injury prevention drills). Two-way analyses of variance were used to assess: handgrip; back extensor strength; medicine ball throw; 30 m sprint times; Modified Illinois change-of-direction (Illinois-MT); four jump tests: squat jump (SJ), countermovement jump (CMJ), countermovement jump with arm swing (CMJA) and five‑jump test (5JT); static (Stork test) and dynamic balance (Y Balance Test); and repeated sprint T-test (RSTT). Results revealed significant gains in handgrip - right (p < 0.001, d = 1.75: large), handgrip - left (p < 0.001, d = 2.52: large), back extensor (p < 0.001, d = 2.01: large), and medicine ball throw (p = 0.002, d = 0.95: large) with EG compared to the CG. The EG also demonstrated greater improvement in sprint performance over 20 m (Δ = 10.6%, p = 0.001, d = 1.07: large) and 30 m (Δ = 7.2%, p < 0.0001, d = 1.56: large) compared to the CG. The EG showed better Illinois-MT (Δ = 5.6%, p = 0.034, d = 0.62: medium) compared to the CG. Further, EG posted significant improvements in the SJ (Δ = 17.3%, p = 0.048, d = 0.58: medium), CMJ (Δ = 17.7%, p = 0.017 d = 0.71: medium), and CMJA (Δ = 16.3%, p = 0.019, d = 0.69: medium) compared to the CG. Similarly, the EG exhibited significant improvement in RSTT best time [p = 0.025, d = 0.66 (medium)], RSTT mean time [p = 0.019, d = 0.69 (medium)] and RSTT total time [p = 0.019, d = 0.69 (medium)] compared to the CG. In conclusion, the 10-week STEB improved the physical abilities in young female handball players.